2009
DOI: 10.1002/cncr.24280
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 study with a daily regimen of the oral mTOR inhibitor RAD001 (everolimus) in patients with metastatic clear cell renal cell cancer

Abstract: BACKGROUND: Everolimus, an oral mammalian target of rapamycin (mTOR) inhibitor, affects tumor growth by blocking growth factor stimulation, arresting cell cycle progression, and inhibiting angiogenesis. mTOR inhibitors and agents with primarily antiangiogenic activity have been shown to have efficacy in renal cell cancer (RCC). This phase 2 study assessed the efficacy of daily oral dosing with everolimus in patients with RCC. METHODS: Patients had confirmed predominantly clear cell RCC; had received ≤1 prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(111 citation statements)
references
References 34 publications
(58 reference statements)
3
103
0
3
Order By: Relevance
“…Previous studies have shown that phase II and III trials have shown antitumor activity and survival advantage in patients with metastatic renal cancers treated with mTORI (Rao et al 2004;Baldo et al 2008;Amato et al 2009;Wang et al 2011). In the transplant population, the clinical effectiveness of mTORI for the prevention and treatment of renal cell carcinomas remained unclear.…”
Section: Management Of Cancer In Kidney Transplant Recipientsmentioning
confidence: 99%
“…Previous studies have shown that phase II and III trials have shown antitumor activity and survival advantage in patients with metastatic renal cancers treated with mTORI (Rao et al 2004;Baldo et al 2008;Amato et al 2009;Wang et al 2011). In the transplant population, the clinical effectiveness of mTORI for the prevention and treatment of renal cell carcinomas remained unclear.…”
Section: Management Of Cancer In Kidney Transplant Recipientsmentioning
confidence: 99%
“…Several novel agents that inhibit the VEGF signalling cascade, such as sorafenib, sunitinib and bevacizumab, have been found to exert significant anti-tumour effects and provide meaningful clinical benefits (Escudier et al, 2007;Hudes et al, 2007;Motzer et al, 2007;Rini et al, 2008). Furthermore, temsirolimus and everolimus, inhibitors of the mammalian target of rapamycin (mTOR), which block the phosphoinositide 3-kinase (PI3K)/AKT signalling pathway involved in numerous cellular functions including cell proliferation, survival and angiogenesis, have been found to be effective agents against advanced RCC in the clinical setting (Hudes et al, 2007;Amato et al, 2009). Although molecular targeting therapies against the VEGF or mTOR signalling pathway have revolutionised the treatment of advanced RCC, no curative therapy has yet been established.…”
mentioning
confidence: 99%
“…It is the recommended first line treatment for patients with advanced mRCC and a poor prognosis according to the Motzer score (1). Another mTOR inhibitor everolimus (RAD001) proved beneficial in a clinical phase II and III study and is regarded as a second line option after failure of tyrosine kinase treatment (2,5). Furthermore, numerous studies provided significant insights into the mTOR pathway and underlined the relevance of mTOR as potential target of anti-cancer therapy (7).…”
Section: Discussionmentioning
confidence: 99%
“…After showing their therapeutic effectiveness in first-and second-line regimens new antiangiogenic drugs have been approved in Europe and in the USA for the treatment of metastatic RCC (mRCC). At present the main targets are multiple tyrosine kinase inhibitors and specific inhibitors of mammalian target of rapamycin (mTOR) (2,3). Among the mTOR inhibitors temsirolimus showed anti-tumor activity in a phase III study compared to interferon-· (IFN)-· (3,4).…”
Section: Introductionmentioning
confidence: 99%